Responsiveness of a balance assessment using a mobile application - Krause, D. A.; Anderson, S. E.; Campbell, G. R.; Davis, S. J.; Tindall, S. W.; Hollman, J. H. (Sports Health: A Multidisciplinary Approach, 2020)
Background: Balance assessment is used by clinicians as part of athlete concussion screening. The King-Devick (K-D) Balance app is designed to provide an objective balance assessment value. The purpose of this study was to investigate the responsiveness of a balance assessment using the K-D Balance app.